Notes on natural and social landscape - Gogin Sias, Gina (2013)
From the knowledge on the Physical and Social Capital Recovery of lomas de Pachacamac project, the present article develops the attitude of respect towards Nature implicitly transmitted through propaganda campaigns, a comprehensive and consistent theoretical framework building, supporting the projects related to the environment and the importance of ecology education in universities. In the present article, the indigenous population is revaluated, since their presence in the world has  allowed the preservation of many ecosystems of great significance to humanity. Finally, the communicator is advised to reflect on his own knowledge, the emergency of mass education in ecological issues and the need to legislate regarding to the use of natural resources.